(untitled) (Internet of Things and Edge Computing Journal, 2021)
Multi-tenant serverless computing environments present unique security challenges due to the shared nature of resources among multiple users. This paper examines the specific security considerations and risk mitigation strategies essential for safeguarding data and applications in such environments. The paper starts by delineating the distinctive characteristics of serverless computing, emphasizing its event-driven, ephemeral nature, and how multi-tenancy exacerbates security concerns by sharing resources across tenants. Traditional security measures like network segmentation and access controls may not suffice in this dynamic context. Subsequently, it explores common security threats prevalent in multi-tenant serverless environments, including unauthorized access, data breaches, denial-of-service attacks, and privilege escalation. These threats stem from various sources such as misconfigured functions, vulnerabilities in shared components, or malicious activities by other tenants. To counteract these threats, a comprehensive framework for risk mitigation is proposed. This framework encompasses proactive measures like minimizing attack surfaces, enforcing least privilege access, and implementing secure coding practices. Additionally, it advocates for detective measures such as runtime monitoring and anomaly detection, alongside responsive actions like incident response protocols and data encryption. Furthermore, the paper delves into specific security controls and best practices tailored for multi-tenant serverless environments. These include function-level isolation, secure dependency management, and encryption for data at rest and in transit. It also explores emerging security technologies like serverless-specific intrusion detection systems and runtime application self-protection solutions. Real-world case studies and incidents are analyzed to validate the efficacy of the proposed framework and security measures. By learning from these cases, organizations can better understand common vulnerabilities and refine their security strategies accordingly. In conclusion, proactive security measures and risk mitigation strategies are imperative for ensuring the integrity, confidentiality, and availability of data and applications in multi-tenant serverless computing environments. As the adoption of serverless continues to rise, ongoing research and collaboration are essential to stay abreast of evolving security threats and challenges.